Podolsky's electromagnetic theory on the null-plane gauge - Bertin, M. C. [UNESP] (2010)
Following the Dirac's technique for constrained systems we performed a detailed analysis of the constraint structure of Podolsky's electromagnetic theory on the null-plane coordinates. The null plane gauge condition was extended to second order theories and appropriate boundary conditions were imposed to guarantee the uniqueness of the inverse of the constraints matrix of the system. Finally, we determined the generalized Dirac brackets of the independent dynamical variables. © 2010 American Institute of Physics.